BERCERMIN PADA BATIK - Friskadewi, Nurul (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
Diversity becomes natural to them who have archipelago geographical condition. We may reflect to cultural product as batik. Batik growth in this nation has received many influences. This influences then creatively combined with our culture and still coloring our cultural lives. The purpose of this paper is to describe cultural diversity by reflecting on batik. Currently batik has spread widely throughout Indonesia and become a national and international identity. Adaptation perspective, various influences can be overcome without leaving the authenticity of this nation. This is in line with the spirit “Bhinneka Tunggal Ika”. Again, reflecting on ourselves, batik is only a material culture which rich in meaning, and most important, how values and meaning can inspired us and generations to come.